2020
DOI: 10.1002/14651858.cd006126.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Tamponade in surgery for retinal detachment associated with proliferative vitreoretinopathy

Abstract: Background-Retinal detachment (RD) with proliferative vitreoretinopathy (PVR) often requires surgery. During surgery, a tamponade agent is needed to reduce the rate of recurrent retinal detachment. Objectives-The objective of this review was to evaluate the benefits and adverse outcomes of surgery with various tamponade agents. Search methods-We searched the Cochrane Controlled Register (CENTRAL), MEDLINE, EMBASE, Latin America and Carribbean Health Sciences (LILACS) and the UK Clinical Trials Gateway (UKCTG).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 57 publications
0
34
1
3
Order By: Relevance
“…Silicone oil of 1000 cSt (sc) viscosity was found to be superior to sulfur hexafluoride in the treatment of complex retinal detachment [6]. In vitro retinal detachment models have shown that increasing silicone oil viscosity increases resistance to volume displacement, a mechanism through which oil tamponades the retina against the retinal pigment epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Silicone oil of 1000 cSt (sc) viscosity was found to be superior to sulfur hexafluoride in the treatment of complex retinal detachment [6]. In vitro retinal detachment models have shown that increasing silicone oil viscosity increases resistance to volume displacement, a mechanism through which oil tamponades the retina against the retinal pigment epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Gastamponaden dienen der temporären intravitrealen Tamponade [9,10,12,13]. Nachdem sich ein Gleichgewicht mit den Blutgasen eingestellt hat und eine Expansion der Gase im Auge stattgefunden hat (außer Luft), wird die Gastamponade mehr oder weniger schnell durch Abdiffusion geringer (▶ Abb.…”
Section: Apparative Voraussetzungenunclassified
“…Results were comparable in long-term outlook to those in which SO was inserted. [ 66 67 ] The SO study concluded that SO was superior to sulfur hexafluoride and roughly equivalent to fluoropropane in cases with RD with severe PVR. [ 67 ]…”
Section: Management Of Recurrent Retinal Detachmentmentioning
confidence: 99%